Dynamic changes in platelet counts and psychological state in ITP patients after COVID-19 infection - Chen, Xiaoli; Wang, Dan; Tang, Jie; Wang, Li; Quan, Yao; Liu, Jia; Zou, Zhongmin; Sun, Hengrui; Feng, Yimei; Zhang, Xi (Frontiers in Medicine, 2025)
IntroductionAt the end of 2022, the COVID-19 wreaked havoc in China as well as around the world. Here, we focused on the dynamic changes in platelet kinetics and psychological state in ITP patients before and after infection with COVID-19.MethodsA questionnaire survey was designed to retrospectively investigate the COVID-19-related symptoms, changes in platelet count, and psychological changes in ITP patients infected with Omicron variant during November 2022 to January 2023, with a healthy population survey conducted as a control.ResultsA total of 90 ITP patients and 69 healthy individuals were included in the study. The results showed that only in terms of low-grade fever, the proportion of ITP patients was significantly higher than that of healthy individuals, 31% vs. 17% (p = 0.04). Interestingly, it was found that there was a transient elevation in platelet counts (PC) of ITP patients after COVID-19 infection, which then gradually decreased to the previous level after recovering from virus, including three subgroups comparation: PC >100 × 109/L vs. PC <100 × 109/L; ITP treatment vs. non-ITP treatment; and vaccination vs. non-vaccination. Additionally, the platelet-to-lymphocyte ratio (PLR) showed the same trend. The fear and concerns related to COVID-19 infection were also compared between the two population. For ITP patients, they are more concerned that COVID-19 will worsen the condition of ITP and delay its recovery. It should be pointed out that the limitations of this study include the small sample size in the retrospective survey and the possibility of selection bias in ITP patients.ConclusionSome ITP patients showed transiently elevated platelet counts after COVID-19 infection, and the specific mechanism requires further exploration. Additionally, ITP patients experienced heightened anxiety and tension after COVID-19 infection, needing for more mental health support.